Implementasi Program Keluarga Harapan (PKH) Dalam Menunjang Pendidikan Siswa Di Desa Jemowo Kabupaten Boyolali - Ari Yohana Pramesti; Eni Rahmawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study analyzes the implementation of the Family Hope Program (Program Keluarga Harapan/PKH) in supporting students' education in Jemowo Village, Boyolali Regency. Previous studies on PKH have mainly discussed program effectiveness at a general level, while local studies that connect program implementation, mentoring practices, family behavior, and educational sustainability in rural settings remain limited. This study used a descriptive qualitative approach involving eight informants, consisting of one PKH facilitator, one village official, two parents from beneficiary families, three student beneficiaries, and one school representative. Data were collected through observation, semi-structured interviews, and documentation. The data were analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data display, and conclusion drawing. Data credibility was strengthened through source triangulation, method triangulation, and member checking. The findings show that PKH implementation in Jemowo Village has been carried out through DTKS-based data validation, non-cash aid distribution through the Family Welfare Card, Family Capacity Building Meetings, home visits, and school attendance monitoring. PKH assistance helps reduce educational expenses, strengthens parents' awareness of schooling, improves students' learning motivation, and supports student attendance. However, the assistance has not fully covered all educational needs because educational sustainability is also influenced by parental awareness, household economic pressure, and the learning environment. The novelty of this study lies in its contextual analysis of PKH implementation at the village level by integrating policy implementation, mentoring, and educational behavior of beneficiary families.